2021
DOI: 10.1186/s12875-021-01390-3
|View full text |Cite
|
Sign up to set email alerts
|

Family medicine residents’ skill levels in emergency chest X-ray interpretation

Abstract: Background Family medicine physicians may encounter a wide variety of conditions, including acute and urgent cases. Considering the limited access to diagnostic investigations in primary care practice, chest X-ray remains the imaging modality of choice. The current study assessed the competency of family medicine residents in the interpretation of chest X-rays for emergency conditions and to compare it with that of diagnostic radiology residents, general practitioners, and medical interns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…On the other hand, other comparable study showed 83.8% of the participants detect the normal CXR. [8] This might be because of the quality of training and multiple exposure of such a case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other comparable study showed 83.8% of the participants detect the normal CXR. [8] This might be because of the quality of training and multiple exposure of such a case.…”
Section: Discussionmentioning
confidence: 99%
“…This survey sought to assess the competency level of medical interns in interpreting common X-ray abnormalities and to explore the barriers and enablers that contribute to the development of adequate X-ray interpretation skills. The study questionnaire was developed by reviewing recent literature and questionnaire used in previous study [8]. The survey's distribution was facilitated with the support of 18 data collectors from different universities, a measure taken to ensure the presence of a sufficiently large participant cohort that effectively represents the target population.…”
Section: Methodsmentioning
confidence: 99%
“…The COVID-19 pandemic may have also contributed to the increased number of chest radiographs performed during the study. 26 …”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic may have also contributed to the increased number of chest radiographs performed during the study. 26 General practitioners reported strong performance in consultation and communication skills, although communication skills are challenging to define and self-assess. 27 Indirect observation of the GPs' consultations in a previous study carried out at these facilities, showed that consultations were brief, bio-medical and lacked a person-centred approach.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…4,11–13 Although systems are often in place for the correction of errors made at the bedside, the final report by a radiologist may not be available in a timely manner to influence immediate decision-making, and in resource limited settings, there may be no radiologist over-read of the pCXR at all. 1,9,14–16…”
mentioning
confidence: 99%